2010
DOI: 10.3113/fai.2010.0797
|View full text |Cite
|
Sign up to set email alerts
|

First Metatarsophalangeal Arthrodesis using a Dorsal Plate and a Compression Screw

Abstract: These results show that arthrodesis of the first MTP joint with spherical reamers and a low-profile contoured dorsal titanium plate and compression screw is highly successful, with excellent patient satisfaction and functional outcomes. We recommend the use of specially designed plates against improvised plates as bending leads to poor control over dorsiflexion and may increase the incidence of plate failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 21 publications
6
66
2
3
Order By: Relevance
“…Different methods of joint surface preparation are described in the literature, including: simple cartilage excision, planar cartilage excision using a saw, cone and socket preparation, and machined conical reaming. Most series have reported high rates of fusion despite the variation in types of fixation and methods of surface preparation [20,25]. Singh et al.…”
Section: Discussionmentioning
confidence: 98%
“…Different methods of joint surface preparation are described in the literature, including: simple cartilage excision, planar cartilage excision using a saw, cone and socket preparation, and machined conical reaming. Most series have reported high rates of fusion despite the variation in types of fixation and methods of surface preparation [20,25]. Singh et al.…”
Section: Discussionmentioning
confidence: 98%
“…Arthrodesis of the first metatarsophalangeal joint is considered to be the gold-standard technique for treating patients with severe hallux valgus, recurrent hallux valgus and deformities secondary to inflammatory arthritis of the hallux (4)(5)(6)(7)(8)(9)(10)20,21) . In a prospective study, Brodsky et al (6) showed that arthrodesis of this joint improved the stability and propulsive force during gait, for feet with severe joint degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which the deformity is considered to be moderate or severe, a proximal approach to the first metatarsal is recommended, with the aim of correcting the varus deformity of this bone. Arthrodesis of the first metatarsophalangeal joint is a treatment option for patients with severe hallux valgus, recurrent hallux valgus and deformities secondary to inflammatory arthritis of the first metatarsophalangeal joint, such as in cases of rheumatoid arthritis (4)(5)(6)(7)(8)(9)(10) . Since arthrodesis does not directly address varus deformity of the first metatarsal, there are doubts in relation to patients with an increased intermetatarsal angle regarding whether the varus deformity can be corrected by means of arthrodesis of the first metatarsophalangeal joint alone, or whether osteotomy at the base of the first metatarsal is necessary (11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…Hallux valgus associated with hypermobility of the first ray can be corrected by arthrodesis of the first tarsometatarsal joint [36]. A first metatarsophalangeal (MTP) joint arthodesis generally is reserved for hallux valgus associated with first MTP joint arthrosis, or severe deformities [1,18,37]. A large IMA in combination with an increased DMAA cannot be corrected with a proximal osteotomy alone; reducing the IMA will effectively increase the DMAA [15].…”
Section: Current Concepts For Primary Operative Treatmentmentioning
confidence: 99%
“…Arthrodesis of the first metatarsophalangeal joint [18,20,37,46] Indications: (1) Revision surgery for instability of the metatarsophalangeal joint (cock-up deformity, floppy toe). (2) Recurrent valgus deformity with arthritis of the metatarsophalangeal joint or with neurological disease.…”
Section: Strategy and Indicationsmentioning
confidence: 99%